2023
DOI: 10.1136/bcr-2022-251896
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral primary breast Burkitt’s lymphoma in pregnancy

Abstract: Pregnancy-associated cancer is defined as malignancy diagnosed during gestation or up to 1 year post partum. Treatment of cancer during pregnancy is complicated by the risk of harm to the fetus and limitations in safety data. Postpartum patients receiving chemotherapy, tyrosine-kinase inhibitors or hormonal agents should avoid breast feeding to avoid drug excretion in breast milk. Patients who will receive cytotoxic chemotherapy should be advised of the potential impact on their future fertility and offered fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Additionally, a study reported a case of basal cell carcinoma following radiotherapy for breast cancer in 2021 (Marques-Antunes et al, 2021). Moreover, the associations between breast cancer and pulmonary sarcoidosis, ischemic diseases, spinal cord injuries, Ewing's sarcoma and Lymphoma have been validated in the literature (Dong et al, 2021;Sawatzky et al, 2021;Altshuler et al, 2023). Collectively, these findings provide further confirmation of the MHIF-MSEA model's ability to accurately identify diseases that traditional enrichment analysis methods may overlook.…”
Section: Case Studies Of Mirna Set Enrichment Analysismentioning
confidence: 66%
“…Additionally, a study reported a case of basal cell carcinoma following radiotherapy for breast cancer in 2021 (Marques-Antunes et al, 2021). Moreover, the associations between breast cancer and pulmonary sarcoidosis, ischemic diseases, spinal cord injuries, Ewing's sarcoma and Lymphoma have been validated in the literature (Dong et al, 2021;Sawatzky et al, 2021;Altshuler et al, 2023). Collectively, these findings provide further confirmation of the MHIF-MSEA model's ability to accurately identify diseases that traditional enrichment analysis methods may overlook.…”
Section: Case Studies Of Mirna Set Enrichment Analysismentioning
confidence: 66%